Sanacja's Foreign Policy and the Second Polish Republic, 1926-1935 - (:unkn) unknown (My University, 2015)
Following its reemergence on the map of Europe in 1919, the Second Polish Republic found itself wedged between a revisionist German state and a world revolution-seeking communist Russia. Although it procured alliances with France and Romania, territorial issues spoiled relations with neighboring states and revisions to the post-World War I order began to raise serious concerns over the Republic’s security in East Central Europe. Seven years later and after the May coup by Marshal Józef Piłsudski, the Sanacja regime emerged as the Republic’s caretaker and instituted an exotic foreign policy that saw Poland become self-dependent and adopt the sub-policy of equilibrium or “równowaga.” This thesis focuses on the formation of Sanacja’s foreign policy during a nine-year period from 1926 to 1935, through the examination of relations between Poland and its allies, perceived enemies, neighbors, and the overall changing political atmosphere in Europe.
Keywords: Foreign Policy; Interwar Poland; Józef Piłsudski; Poland; Równowaga; Sanacja